A retrospective analysis of small molecule targeting inhibitor usage for lung cancer among outpatients in six major regions of China (2016–2022) - Chen, Bo; Wang, Chen; Chen, Li-Ying; Hu, Yan; Wang, Yu-Zhen; Li, Liu-Cheng; Mao, Kai-Li; Jiang, Qiu (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate national trends in amounts, prescription volumes, and the rationality of drug use in pharmacoeconomics associated with small molecule targeting inhibitors for lung cancer treatment among adult patients in China from 2016 to 2022.MethodsPrescription data for outpatients diagnosed with lung cancer were extracted from the Hospital Prescription Analysis Cooperative Project database, covering hospitals across six major regions of 77 hospitals. Annual trends in prescription volumes and associated expenditures were analyzed. Additionally, pharmacoeconomic indicators related to small molecule targeting inhibitors were assessed to evaluate cost-effectiveness and utilization patterns. Demographic profiles, regional sources of patients, and classification of small molecule targeting inhibitors were examined.ResultsPrescription volumes and amounts for small molecule targeting inhibitors in lung cancer treatment have increased annually. Since 2020, expenditure levels have stabilized. Furthermore, their use is supported by pharmacoeconomic evidence indicating rational and efficient medication utilization. There was a statistically significant increase in total prescriptions (P1 < 0.001) and overall medication expenditures (P2 < 0.001).ConclusionBetween 2016 and 2022, the prescription volume of small molecule targeted inhibitors for lung cancer rose yearly, showing their expanding clinical use. Since 2020, despite continued growth in prescriptions, drug costs have stabilized or slightly decreased. This reflects that China’s medical insurance negotiation and centralized procurement policies have effectively reduced patients’ economic burden without limiting their access to these inhibitors. Pharmacoeconomic indicators also confirm that the use of these drugs has been both reasonable and efficient, allowing for increased drug utilization while reducing patients’ financial strain.